The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s40200-017-0298-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome and health-related quality of life in war-related bilateral lower limb amputees

Abstract: BackgroundLower limb amputation is correlated with considerable impairments in health-related quality of life (HRQOL) in veterans. The aim of this study is to determine the prevalence of metabolic syndrome (MetS) in veterans with bilateral lower limb amputation and to identify its association with HRQOL.MethodsThis cross-sectional study was conducted on 235 Iranian male veterans with bilateral lower limb amputation. Demographics, anthropometrics, and biochemical measurements were assessed and MetS was defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
12
0
2
Order By: Relevance
“…Only one cross sectional study reported metabolic syndrome as a specific outcome. Etjahed and colleagues observed a 2-fold higher risk of metabolic syndrome (Defined according to the ATP III Criteria) [45] among 235 veterans with bilateral traumatic lower limb amputation versus controls from the general population (high ROB) [46].…”
Section: Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Only one cross sectional study reported metabolic syndrome as a specific outcome. Etjahed and colleagues observed a 2-fold higher risk of metabolic syndrome (Defined according to the ATP III Criteria) [45] among 235 veterans with bilateral traumatic lower limb amputation versus controls from the general population (high ROB) [46].…”
Section: Metabolic Syndromementioning
confidence: 99%
“…Comparative lipid levels and risk of hyperlipidaemia were reported in 11 studies. Among TI veterans two studies (cross sectional) reported an increased lipid profile compared with controls (high ROB) [37,46]. ere were six (two cohort and four cross sectional) studies that all reported no difference in lipid levels or risk of hyperlipidaemia among combatants with TI versus controls of TI (3 moderate and three high ROB) [19, 24-26, 34, 39].…”
Section: Blood Lipid Levelsmentioning
confidence: 99%
“…A high BMI is also common in persons with LLA [15,16]. Studies in persons with SCI or LLA report prevalence rates of overweight, obesity and metabolic syndrome ranging from 43 to 75 percent [14,[16][17][18][19][20]. An increased BMI is a leading cause of preventable deaths due to the relation with cardiovascular diseases and several other (chronic) diseases [1,21].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have recently associated MSy, QoL, and CPL (13,20,45). Because MSy is frequently associated with obesity and overweight, the concomitant poor QoL and CPL can frequently hamper these patients in performing the normal daily activities (19,58).…”
Section: Discussionmentioning
confidence: 99%